1996
DOI: 10.1063/1.470762
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of solvent clusters in a supercritical Lennard-Jones fluid

Abstract: We have developed a new methodology for characterizing the solvent cluster structures which occur in a pure supercritical fluid in its compressible regime. This methodology takes advantage of the time scale separation which exists between collective-cluster and individual-solvent–atom motions in order to classify atoms according to their ‘‘instantaneous’’ local environments. The resultant picture is of a fluid having density inhomogeneities on a mesoscopic length scale—i.e., clusters and cavities. Calculation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 43 publications
1
44
0
Order By: Relevance
“…In order to quantify the clustering of hydrophobic neopentane molecules and the possible effects of trehalose and temperature on it, we have estimated the average cluster size in all systems simulated here. For this, we have adopted the method employed by Martinez et al 50 for a Lennard-Jones uid. Our group in the simulation study of methane aggregation in aqueous osmolyte solutions successfully employed this method later.…”
Section: B Neopentane Cluster Structure Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In order to quantify the clustering of hydrophobic neopentane molecules and the possible effects of trehalose and temperature on it, we have estimated the average cluster size in all systems simulated here. For this, we have adopted the method employed by Martinez et al 50 for a Lennard-Jones uid. Our group in the simulation study of methane aggregation in aqueous osmolyte solutions successfully employed this method later.…”
Section: B Neopentane Cluster Structure Analysismentioning
confidence: 99%
“…Note that, in order to calculate the number of molecules in the solvation sphere (n) we have integrated the neopentane-neopentane pair correlation function up to the rst minimum. And for calculating the average number of molecules (n 0 ), we have adopted the method proposed by Martinez et al 50 We set the uctuation, d, at 20% of the average number of molecules (n 0 ).…”
Section: B Neopentane Cluster Structure Analysismentioning
confidence: 99%
“…An important note is that these authors observed a decrease in N ex at large distances from the ions, indicating a depletion in solvent density relative to the bulk value, as a result of the finite number of molecules in the NVT simulation cell. This artificial depletion of density at long-range induces an effective pressure on the solute-induced local density enhancement, tending to reduce its size 14 Average number of excess water molecules found, via molecular dynamics simulation, (a) surrounding a central water, sodium, and chloride particle, and (b) surrounding a central water, argon, and methanol particle, at T r = 1.05 and ρ r = 1.00 (state 2).…”
Section: Theoretical and Computational Studiesmentioning
confidence: 99%
“…Until now, we have focused on the average local densities found around solutes (or tagged solvent molecules) in SCFs. However, a number of investigators ,,,,,,, have used computer simulation to determine the distribution of local environments, i.e. of local densities, experienced by the solute in the equilibrium ensemble.…”
Section: B Distributions Of Local Environments1 Simulationmentioning
confidence: 99%
“…Previously, molecular simulations were used for studying SC fluids in the bulk (Shing and Chung, 1987;Nouacer and Shing, 1989;Cummings et al, 1991;Chung and Shing, 1992; Eckert et al, 1996;Martinez et al, 1996; Yoshii and Okazaki, 1997; for a review see Chialvo and Cummings, 1999), very few such studies were devoted to investigating the behavior of SC fluids in small pores (Nicholson, 1998). They were mostly based on the MC method (Nitta and Yoneya, 1995; Shigeta et al, 1996).…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%